2015
DOI: 10.1002/jcp.24934
|View full text |Cite
|
Sign up to set email alerts
|

Y‐box Binding Protein‐1 Is Part of a Complex Molecular Network Linking ΔNp63α to the PI3K/akt Pathway in Cutaneous Squamous Cell Carcinoma

Abstract: Cutaneous squamous cell carcinomas (SCCs) typically lack somatic oncogene-activating mutations and most of them contain p53 mutations. However, the presence of p53 mutations in skin premalignant lesions suggests that these represent early events during tumor progression and additional alterations may be required for SCC development. SCC cells frequently express high levels of ΔNp63α and Y-box binding 1 (YB-1 or YBX1) oncoproteins. Here, we show that knockdown of YB-1 in spontaneously immortalized HaCaT and non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 34 publications
(45 reference statements)
0
24
0
Order By: Relevance
“…) and YB‐1 increases ΔNp63 α mRNA and protein level (Troiano et al . ), our latest information indicates the existence of a reciprocal positive control between ΔNp63 α and YB‐1 as we have schematically represented in Fig. .…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…) and YB‐1 increases ΔNp63 α mRNA and protein level (Troiano et al . ), our latest information indicates the existence of a reciprocal positive control between ΔNp63 α and YB‐1 as we have schematically represented in Fig. .…”
Section: Discussionmentioning
confidence: 83%
“…), whereas YB‐1 silencing induces apoptosis in mitotically active HaCaT keratinocytes (Troiano et al . ).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Phosphorylation of YB-1 S102 activates the translation of mRNA involved in growth and survival, while direct phosphorylation or subsequent stress induces nuclear localization enabling YB-1 to exert transcriptional control on a further subset of genes, including those involved in drug resistance (16,45). In contrast to results from studies on squamous carcinoma cells (46), reduced leukemia cell viability was not observed following YB-1 knockdown alone. The current study, however, implicates the activation of YB-1 by IL-7 as a mechanism contributing to the survival of BCP ALL in the presence of cytotoxic stressors.…”
Section: A B Cmentioning
confidence: 57%